Capitalist development in the twentieth century : an evolutionary-Keynesian analysis - Cornwall, John (Modern Cambridge Economics Series., 2001)
Twentieth-century capitalism is marked by alternating bad and good performance. The authors consider the macroeconomic record of the developed capitalist economies over the past 100 years (including rates of growth, inflation, unemployment) and the interaction of economic variables with changing structural features of the economy during industrialization and transformation.